Seguimiento clínico de pacientes con psoriasis en las Termas de Copahue (Neuquen-Argentina) - Ubogui, Javier; Roma, Andrés; Garvier, Verónica; García, Fernanda; Perrotta, Gabriela; Monasterio, Ana (Anales de Hidrología Médica, 2008)
Copahue-Coviahue are the most reknown Argentinian therms for the therapeutic benefits related to different dermatological, osteoarticularmuscular, and respiratory diseases. The method used to document the results of psoriatic patients receiving treatment in the thermal station was to compile all the clinical data before and after their stay and compare them. P.A.S.I. was used because it is considered internationally the most standard method for an objective therapeutic evaluation of psoriatic patients. Two important limitations of this therapy are the brief period of the year that one can access the spa (between december and april) and the patient tendency to short stays. Due to its volcanic origin, a great variety of waters, algae, vapors, and muds are present in different combination schemes. Our psoriatic patients were treated with a sulphurous water called “Green Water” (due to a suspension of microalgae that develop in the natural spring), a type of grey sulphurous mud, and thermophile algae. Our conclusion is that the inexistent toxicity and the pleasant experience of balneotherapy in Copahue-Caviahue justifies its consideration as a complementary method in combined, rotating and sequential plans for psoriatic patient treatment.
Keywords: Balneology; Psoriasis; Balneotherapy; Fangotherapy; Mud therapy; Copahue